2021
DOI: 10.1111/tan.14349
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐A homozygosis is associated with susceptibility to COVID‐19

Abstract: The purpose of this single center retrospective study was to investigate the relationship between HLA and ABO polymorphisms and COVID‐19 susceptibility and severity in kidney transplant recipients. It included 720 recipients who had COVID‐19 and 1680 controls composed by recipients in follow‐up who did not contact the transplantation center for COVID‐19 symptoms, up to the moment of their inclusion in the study. HLA‐A, ‐B, and ‐DRB1 allele groups and ABO frequencies were compared between recipients with COVID‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…The following are available online at https://www.mdpi.com/article/10 .3390/ijms23031583/s1. References [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] are cited in the Supplementary Materials. Informed Consent Statement: Informed consent was obtained from all subjects involved in the study.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The following are available online at https://www.mdpi.com/article/10 .3390/ijms23031583/s1. References [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] are cited in the Supplementary Materials. Informed Consent Statement: Informed consent was obtained from all subjects involved in the study.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…In studies carried out in a Brazilian population [16] , a higher susceptibility was shown for the individuals who were homozygous for the entire HLA-A locus.…”
Section: Discussionmentioning
confidence: 94%
“…Six types of approaches were observed when it came to data sourcing for analysis, including both dry lab and wet lab, which are briefly discussed here—(i) HLA typing for both patient and control group were carried out in wet lab, frequency of different alleles were compared between two groups for any significant differences with different outcomes ( n = 9) 2,14,17,18,25,27,29,31,42 ; (ii) the most frequent HLA alleles were retrieved from AFND for the concerned countries of respected studies, SARS‐CoV‐2 genome was downloaded from NCBI or national databases and peptide binding capacity of frequent alleles was then evaluated using different version of NetMHCpan web server, association of strongly or weakly bound peptides with COVID cases and deaths per million (from worldometer, WHO situation report) were analyzed further through frequency analysis of HLA alleles, as it is established that strongly bound peptide are better presented and weakly bound peptides are poorly presented by MHC to T‐cells and thus can play a major role in adequate immune responses against COVID ( n = 6) 12,13,19–22 ; (iii) HLA allele frequency data for both patient and control group were obtained from national organ donor registry and COVID data from worldometer or national COVID registry, compared allele frequency between healthy and COVID group for identifying any association with COVID susceptibility or among mild, moderate or severe groups of COVID patients to associate HLA with COVID severity and/or mortality ( n = 9) 6,11,28,33,36,38,41,43,44 ; (iv) HLA typing in wet lab was opted for the patient group but reference group were selected from the population with known HLA type through donor registry and after that association with COVID susceptibility, severity or mortality were analyzed ( n = 6) 5,24,26,32,34,45 ; (v) in this approach, metagenomics data from patients were used to predict HLA type using HLA prediction software (HLAminer, OptiType, Seq2HLA, etc.) with or without control group ( n = 4) 1,23,35,40 ; (vi) lastly, two studies observed human monocyte HLA‐DR (mHLA‐DR) expression among healthy people and different clinical stages of COVID patients to identify any impact of altered mHLA‐DR expression with COVID‐19 prognosis ( n = 2) 37,39 (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Six types of approaches were observed when it came to data sourcing for analysis, including both dry lab and wet lab, which are briefly discussed here-(i) HLA typing for both patient and control group were carried out in wet 6,11,28,33,36,38,41,43,44 ; (iv) HLA typing in wet lab was opted for the patient group but reference group were selected from the population with known HLA type through donor registry and after that association with COVID susceptibility, severity or mortality were analyzed (n = 6) 5,24,26,32,34,45 ; (v) in this approach, metagenomics data from patients were used to predict HLA type using HLA prediction software (HLAminer, OptiType, Seq2HLA, etc.) with or without control group (n = 4) 1,23,35,40 ; (vi) lastly, two studies observed human monocyte HLA-DR (mHLA-DR) expression among healthy people and different clinical stages of COVID patients to identify any impact of altered mHLA-DR expression with COVID-19 prognosis (n = 2) 37,39 (Tables 1 and 2).…”
Section: Heterogeneity In Hla Sources and Approaches For Association ...mentioning
confidence: 99%
See 1 more Smart Citation